Computational Analysis of Evacuation Planning for Emergency Situations by Using Crowd Behavior Simulator for Disaster Evacuation (CBS-DE) - MOHAMMAD SYAFUAN BIN JAILANI (Recent Trends in Civil Engineering and Built Environment, 2022)
Over the past few decades, various occurrences of natural disaster have been recorded, even in Malaysia natural disaster are happening yearly as the history documented, this clearly highlighting the importance of evacuation planning. Evacuation plan does not only limiting to counter the natural disaster, however it also applicable towards all the emergency occurrences including man-made disaster such as infrastructure mishaps. It is utterly clear that panic due to fear will arise among the crowd during an emergency; this will lead to few complications such as stampede that probably causing serious injury toward the individuals. Unfortunately, this is a natural human survival instinct. Chances of surviving an emergency situation might increase with an efficient and effective evacuation planning. The advancement of the computer technology has speed up and increases the capability of the development of evacuation planning. Crowd behavior simulator model could be used for several applications especially to tackle and solve the multiple problems that happen during an emergency evacuation and increase survival chances of the crowd at the same time. The modelling is created using a DEM-based crowd behavior simulator, Crowd Behavior Simulator for Disaster Evacuation (CBS-DE), this simulator enabling user to analyze the evacuation plan. Thus, the main objective of this study is to investigate the effectiveness and efficiency of evacuation process by application of this simulator. The scenario was carried out using the average walking speed of Malaysian that is 1.16 m/s. The result from the crowd behavior simulator was analyzed to determine the effectiveness and the efficiency of the simulator.